KLASIFIKASI ABSTRAK JURNAL KOMPUTASI MENGGUNAKAN METODE TEXT MINING DAN ALGORITMA SUPPORT VECTOR MACHINE - Eliza Fitri; Favorisen R. Lumbanraja; Ardiansyah Ardiansyah (Jurnal Pepadun, 2020)
The University of Lampung especially Computer Science Departement has an online journal that publishes various scientific articles written by researchers both students and lecturers. This scientific article is called the online Computating Journal which is published once every 6 months. But, this online Computating Journal has not been structured and classified into the category of science that more specific. Therefore, in this research the abstract Computating Journal will be classified using text mining techniques to process the abstract become more structured and retrieve information in it. Then, the information in the abstract is extracted as a feature by the TFIDF weighting technique. The proposed classification model uses the support vector machine algorithm that has strong consistency. The model classification will be validated by applying the 10-Fold Cross Validation technique.